1969
DOI: 10.1128/aem.17.2.252-255.1969
|View full text |Cite
|
Sign up to set email alerts
|

Marine Microorganisms Associated with the Food of Young Salmon

Abstract: The biomass of microorganisms in the digestive tracts of young salmon in the sea of Saanich Inlet was examined by (i) the direct microscopic method, (ii) the plate count method and (iii) the physiological method (microbial biomass assumed from the release of carbon dioxide). By all methods, most microbial biomass in foods was shown to decrease during its stay in the digestive organ. This observation was supported by the detection of many bacteria at different stages of digestion. The microbial biomass was quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

1970
1970
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
1
11
1
Order By: Relevance
“…The bacterial genera present within the alimentary tract may possibly be a reflection of those genera present on the food ingested (Shewan, 1961;Seki, 1969). After examining 11 species of fish from the North Atlantic, Gibbons (1934) concludedthat the bacterial floras of the skin and faeces were similar; members of the genera Achromobacter and Micrococcus were the most numerous strains present.…”
Section: R W Horsleymentioning
confidence: 99%
“…The bacterial genera present within the alimentary tract may possibly be a reflection of those genera present on the food ingested (Shewan, 1961;Seki, 1969). After examining 11 species of fish from the North Atlantic, Gibbons (1934) concludedthat the bacterial floras of the skin and faeces were similar; members of the genera Achromobacter and Micrococcus were the most numerous strains present.…”
Section: R W Horsleymentioning
confidence: 99%
“…Aquatic bacteria belong to a large diversity of taxonomic groups. According to Seki (1969), only 30% of the bacteria in aquatic systems are found as free-living bacteria. The majority are found as aggregates around an organic core (dead organisms, faecal pellets, molts of zooplankton, living phyto-and zooplankton (Porter et al 1983;Crump & Baross 1996;Selmi 2001;Grossart 2010;Tang et al 2010), as well as around an inorganic core, such as clay particles (Attramadal et al 2012) that tend to sink (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors described how the intestinal microflora of fish was related to the microbial composition of the food ingested and of the water (Seki 1969;Tanasomwang and Muroga 1988;Blanch et al 1997). Others reported that the bacterial microbiota of farmed fish were not consistent with those in the water or the diet of the fish (Campbell and Buswell 1983;Muroga et al 1987;Nicolas et al 1989;Montes et al 2006).…”
Section: Introductionmentioning
confidence: 99%